WEBINAR KENALI DIRI, RAIH MIMPI KEPADA SISWA SMKK BPK PENABUR BANDARLAMPUNG - Patrisia, Ineke; Juniarta, Juniarta; Eka, Ni Gusti Ayu; Sitanggang, Yenni; Nugroho, Dwi Yulianto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Teachers from SMKK BPK Penabur Bandarlampung have challenges in teaching new students during the Covid-19 pandemic (grade X). They expressed difficulty in recognizing students' learning styles to be able to provide effective learning for students. This PkM activity aims to assess learning styles, student aspirations and conduct webinar activities in an effort to recognize self-concept, career development and learning styles to students and teachers. Before the webinar was held, the PkM team provided a questionnaire that had to be filled out by class X students and the results of the entries were analyzed by a psychologist. Based on the entries related to learning styles, it was found that 66% of 65 class X students have a major learning style with 56% having an auditory learning style. In the minor learning style, most students (50%) of class X have a visual learning style. Based on the entries related to dreams, it was found that 38.4% of students wanted to become entrepreneurs. The webinar activity went well with a total of 199 participants consisting of teachers and students, 60.4% of participants were female. Evaluation assessment from participants (72.4%) strongly agreed that the activity was very useful. The webinar activity focused on discussing the results of the questionnaire that had been filled out by class X. Other participants from classes XI and XII wanted to be able to find out learning styles so that this was made into a follow-up plan.